Flail chest stabilization with Nuss operation in presence of multiple myeloma - Lee, Song Am; Hwang, Jae Joon; Chee, Hyun Keun; Kim, Yo Han; Lee, Woo Surng (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
Nowadays the Nuss operation has been widely adopted as a minimally invasive procedure and standard surgical choice in pectus excavatum. However, much debate and concern have been raised regarding its applicability in adults with pectus excavatum flail chest and other thoratic wall deformities, as compared with younger patients, in terms of complications after surgery. To stabilize the segment of paradoxical chest wall movement we performed the Nuss operation on a patient with multiple myeloma who sustained blunt thoracic trauma. The patient presented with paradoxical movement of the thoracic wall and sternum instability due to multiple myeloma, which led to severe dyspnea, hypoxemia, hypercapnea, and bedridden state. His condition progressed to acute respiratory distress syndrome and did not respond to conservative treatment. We performed the Nuss operation on the patient, and his clinical symptoms were relieved after surgery. The patient regained the ability to walk unassisted and was discharged from the hospital without any specific events.